Innovative project design-based learning: Enhancing students’ critical thinking skills and sciencepreneurship for sustainable science education in junior high school - Astutik, Julia; Sutoyo, Suyatno; Lutfi, Achmad; Fadzillah, Nurrulhidayah Ahmad (Edelweiss Applied Science and Technology, 2026)
Education in the era of the Industrial Revolution 4.0 is required to equip students with 21st-century competencies, including critical thinking skills and sciencepreneurship. This study aims to develop an innovative IPDBL learning model that is effective in enhancing students’ critical thinking skills and sciencepreneurship. This study employed educational development research based on McKenney’s development model. A total of 99 eighth-grade students at the Indonesian School of Kuala Lumpur, Malaysia, participated in this study, divided into one control class (n = 30) and three experimental classes, each comprising 23 students. Data were collected through expert validation and tests of critical thinking skills (CTS) and sciencepreneurship. The obtained data were analyzed using Aiken’s V, percentage of agreement (PA), N-gain score, and Kruskal–Wallis tests. The results showed that the IPDBL learning model and its teaching materials (lesson plans, student books, student worksheets, CTS test, and sciencepreneurship test) were valid and reliable. Based on the N-gain scores and Kruskal–Wallis tests, it can be concluded that the IPDBL learning model was very effective in improving students’ CTS and sciencepreneurship. The implication of this study is that the IPDBL learning model can be considered an alternative innovative approach for sustainable science learning.